The effect of laser welding parameters on mechanical properties and microstructure evolution of multi-layered 6061 aluminum alloy - Shoeib Karami; Mohammad Yousefieh; Homam Naffakh-Moosavy (Journal of Advanced Joining Processes)
In this study, the key findings of evaluating laser beam welding parameters on the multi-layered structure of 6061 aluminum alloys fabricating by accumulative roll bonding process are reported, considering fostering mechanical properties concerning the influence of filler metal and welding speed on the weld bead quality by taking into account reducing welding defects. Welding defects, including porosity and hot cracks, formed due to the evaporation of low-molten elements such as Mg, which can be reduced by adding filler metal to compensate for the vaporized Mg content. The optimal tensile strength is related to the laser beam welding using filler metal at the speed of 40 mm/s. Work-hardening behavior leading to fatigue life improvement is associated with the rearrangement and multiplication of dislocations in all samples. The related mechanisms responsible for the microstructural evolution during the cyclic deformation process were described by transmission electron microscopy observation. The fracture surface analyzed by scanning electron microscopy indicated that delamination contributing to local necking is the leading cause of fracture in accumulative roll-bonded 6061 aluminum alloy. However, the fracture morphology of laser-welded samples displays a heterogeneous distribution of equiaxed dimples along with negligible serpentine sliding, indicating a ductile fracture mode.